Institutional Voids, Economic Adversity and Inter‐firm Cooperation in an Emerging Market: The Mediating Role of Government R&D Support. (26th October 2020) - Adomako, Samuel; Amankwah‐Amoah, Joseph; Debrah, Yaw A.; Khan, Zaheer; Chu, Irene; Robinson, Catherine
Abstract: This paper examines the mediating mechanism of the relationship between institutional voids (IVs) and inter‐firm cooperation and the moderating role of economic adversity in the context of small and medium‐sized enterprises (SMEs) based in emerging markets. The hypotheses are tested using time‐lagged survey data from 214 SMEs in Ghana. The findings provide support for the hypotheses by showing that: (1) IVs positively influence the use of government research and development (R&D) support; (2) the use of government R&D support mediates the relationship between IVs and inter‐firm cooperation; and (3) economic adversity positively moderates the relationship between IVs and the use of government R&D support. The findings contribute to understanding the role of IVs in inter‐firm cooperation. The wider implications for theory and practice are examined.